Bionic intervertebral disc material and preparation method thereof
By using a combination of micro-nano fiber composite membrane and gel nucleus pulposus structure in bionic intervertebral disc materials, the problem of insufficient mechanical properties of bionic intervertebral disc materials in the prior art is solved, and the structural stability and anti-compression performance are improved. Reconstruct the intervertebral disc function.
Patent Information
- Application Number
- CN202411347267.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-13
AI Technical Summary
Existing bionic intervertebral disc materials are difficult to replicate the full-scale structure and macroscopic mechanical properties of natural intervertebral discs, resulting in insufficient in the functional reconstruction of intervertebral discs.
The micro-nano fiber dispersion and sodium alginate are mixed to form a micro-nano composite film. The micro-nano fibers are arranged in an oriented manner through one-way brushing to form an outer fiber annular ring of multi-layer fiber sheets, and combined with the gel nucleus pulposus structure. Bionic disc material is formed by cryoforming and cross-linking.
It has achieved improvements in structural stability, resilience and anti-compression properties of bionic intervertebral disc materials, imitated the mechanical properties of natural intervertebral discs, and is suitable for the treatment of degenerative diseases of intervertebral discs.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material chemistry, and in particular to a bionic intervertebral disc material and a preparation method thereof. Background Art
[0002] Degenerative disc disease is a common and frequently occurring disease in middle-aged and elderly patients, with clinical manifestations of cervical and lumbar back pain, limb pain and sensory disturbances. Severe disc degeneration will significantly affect the patient's life and requires surgical intervention. Discectomy and lumbar fusion are common clinical methods for treating degenerative disc disease with the help of autologous bone and / or biomaterials. Currently, although the polyetheretherketone material used in clinical practice is effective in relieving back pain in the short term, it is difficult to restore the normal biological function and mechanical properties of the disc, sacrificing the flexibility of the disc itself.
[0003] In recent years, bioactive lumbar fusion scaffolds have been developed to perform the functions of support, reinforcement and tissue regeneration. For example, researchers used directional freezing technology to create a silk protein layered three-dimensional scaffold to simulate the natural layered structure of the annulus fibrosus, and constructed agarose gel that mimics the nucleus pulposus to prepare a bionic intervertebral disc structural material with a certain compression modulus (499.18± 86.45 kPa), achieving effective cell proliferation. In addition, the researchers also used 3D printing technology to prepare a unidirectionally arranged cellulose framework, and then combined it with nanocomposite hydrogel to construct a complete wood frame bionic intervertebral disc material.
[0004] Although important progress has been made in the research of bionic intervertebral disc materials, there is still a lack of full-scale imitation of the complex structure of the intervertebral disc to achieve similar mechanical functions. The natural intervertebral disc is mainly composed of a highly hydrated gel nucleus pulposus in the center and an outer annulus fibrosus. The nucleus pulposus is mainly composed of water, reticular collagen fibers and proteoglycan matrix, which provides osmotic pressure to resist compression. The outer annulus fibrosus consists of 15 to 25 concentric layers, and the collagen fibers in each layer are highly oriented and deflected, which helps to resist tensile loads. This complex structure gives the intervertebral disc the ability to resist complex loads. Therefore, by simulating the full-scale structure of the natural intervertebral disc, that is, the outer annular and nucleus pulposus structures, researchers are expected to replicate the unique properties of the natural intervertebral disc in the new bionic intervertebral disc and help reconstruct the function of the intervertebral disc. Unfortunately, the research on bionic intervertebral disc materials that reproduce the microstructure and macroscopic mechanical properties of natural intervertebral disc tissue still needs to be further explored. Summary of the invention
[0005] In view of this, the present invention provides a bionic intervertebral disc material and a preparation method thereof. The bionic intervertebral disc material provided in the present application has an outer annulus fibrosus and a porous gel-state nucleus pulposus structure, and has good structural stability, resilience and compression resistance.
[0006] The present application provides a method for preparing a bionic intervertebral disc material, comprising the following steps:
[0007] a) mixing a micro-nano fiber dispersion and sodium alginate, and applying unidirectionally on a substrate to orient the micro-nano fibers in the sodium alginate matrix to obtain a micro-nano composite membrane; the micro-nano fibers include hydroxyapatite micron fiber bundles and calcium silicate nanofibers;
[0008] The mass ratio of the sodium alginate matrix, the hydroxyapatite microfiber bundle and the calcium silicate nanofiber is 8:2:0.1-3;
[0009] b) keeping the orientation arrangement direction of the micro-nano fibers at an angle to the horizontal direction, and curling the micro-nano composite film into a ring under the action of an adhesive to form an outer fiber ring having multiple fiber sheets;
[0010] c) adding the raw material for forming the gel nucleus pulposus into the cavity of the outer annulus fibrosus, freeze-forming and cross-linking to form the gel nucleus pulposus, thereby obtaining the bionic intervertebral disc material.
[0011] The present application adopts hydroxyapatite micron fiber bundles and calcium silicate nanofibers as reinforcing materials for the outer fiber ring material. The nanofibers are filled in the gaps of the directionally arranged micron fibers, thereby improving the utilization efficiency of the organic-inorganic interface. Compared with the bionic intervertebral disc material prepared by only containing one type of micron fiber or one type of nanofiber, synergistic reinforcement is achieved and the material has stronger mechanical properties.
[0012] The present application first mixes a micro-nano fiber dispersion and sodium alginate to form a mixed solution, wherein the micro-nano fiber dispersion includes a hydroxyapatite micron fiber bundle dispersion and a calcium silicate nanofiber dispersion, wherein the hydroxyapatite micron fiber bundle dispersion is a dispersion of hydroxyapatite micron fiber bundles in water, and the present application has no special restrictions on its concentration; the calcium silicate nanofiber dispersion is a dispersion of calcium silicate nanofibers in water, and the present application has no special restrictions on its concentration. In some specific implementations, the hydroxyapatite micron fiber bundle is a micron-level fiber bundle formed by self-assembly of hydroxyapatite fibers, the diameter of the hydroxyapatite fibers is 15nm~30nm, the diameter of the fiber bundle formed by self-assembly is 1μm~2μm, and the length is more than 20μm. In some specific implementations, the calcium silicate nanofiber is a nanometer-level fiber with a diameter of 20nm~30nm and a length of 2μm~3μm.
[0013] The present application has no special restrictions on the source of the hydroxyapatite micron fiber bundle, which can be purchased from the market or prepared according to the following method:
[0014] The HAP micron fiber bundle is synthesized by a calcium oleate precursor solvothermal method, which specifically includes the following steps:
[0015] mixing sodium hydroxide, oleic acid, methanol and water to obtain a mixed solution;
[0016] mixing the mixed solution with a calcium chloride aqueous solution to obtain calcium oleate;
[0017] The calcium oleate is mixed with a sodium dihydrogen phosphate solution to obtain calcium phosphate after reaction;
[0018] After the calcium phosphate is heated, a hydroxyapatite micron fiber bundle is obtained.
[0019] A typical method for preparing hydroxyapatite micron fiber bundles includes the following steps:
[0020] A NaOH (6.3 g) aqueous solution (90 mL) was slowly dripped into a mixed solution of oleic acid (63 mL), methanol (36 mL) and deionized water (81 mL) and stirred vigorously for 30 minutes. Secondly, a CaCl2 (2 g) aqueous solution (72 mL) was slowly added to the above mixture and stirred for 30 minutes to complete the ion exchange and form calcium oleate. Thirdly, a NaH2PO4•2H2O (5.62 g) aqueous solution (108 mL) was dripped into the above mixture and reacted for 30 minutes to produce amorphous calcium phosphate. The obtained precursor suspension was transferred to a 500 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 180 °C for 24 hours. After the autoclave was cooled to room temperature, the HAP fibers at the bottom were collected, washed three times with ethanol and deionized water respectively, and then dispersed in deionized water.
[0021] The present application has no special restrictions on the source of the calcium silicate nanofibers, which can be purchased from the market or prepared according to the following method:
[0022] The calcium nitrate aqueous solution and the sodium silicate aqueous solution are mixed and reacted, and then heated to react to obtain calcium silicate nanofibers.
[0023] A typical method for preparing calcium silicate nanofibers includes the following steps:
[0024] Ca(NO3)2•4H2O (23.6 g) aqueous solution (200 mL) was added dropwise to NaSiO3•9H2O (28.42 g) aqueous solution (200 mL). After reacting for 30 min, it was transferred to a 500 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 200 °C for 24 h. After the autoclave was cooled to room temperature, the CS fibers at the bottom were collected, washed three times with deionized water, and then dispersed in deionized water.
[0025] After mixing hydroxyapatite micron fiber bundle dispersion, calcium silicate nanofiber dispersion and sodium alginate, preferably vacuumize to remove bubbles in the mixed solution, then unidirectional brushing is performed on the substrate to orient the hydroxyapatite micron fiber bundle and calcium silicate nanofiber in the sodium alginate matrix to obtain a micro-nano composite film. When brushing, the shear force generated by brushing can induce the micro-nano fiber orientation in the liquid phase system, thereby forming an oriented fiber sheet. In some specific implementations, multiple unidirectional brushing is performed on the substrate, such as brushing 10 times or 15 times, to obtain a micro-nano composite film. In some specific implementations, a commercial brush is used to adsorb the mixed solution and then unidirectional brushing is performed on the substrate.
[0026] In some specific implementations, the substrate may be a glass substrate, which is preheated to 50° C. to 100° C., more preferably to 60° C. to 90° C., and most preferably to 80° C. In some specific implementations, the brushing speed is preferably 1 cm / s to 5 cm / s, preferably 2 cm / s.
[0027] In some specific implementations, after unidirectional brushing in the first direction, unidirectional brushing in the second direction is continued, and the first direction and the second direction form an angle, so that the orientation arrangement direction of the micro-nano fibers (including hydroxyapatite micron fiber bundles and calcium silicate nanofibers) in the sodium alginate matrix changes, and a micro-nano composite film with cross-distribution of micro-nano fibers is obtained, thereby enhancing the mechanical properties of the bionic intervertebral disc material. This application has no special restrictions on the unidirectional brushing parameters of the second direction, and the parameters described above can be referred to. In some specific implementations, the angle between the first direction and the second direction is 90°.
[0028] In some specific implementations, the mass ratio of the sodium alginate matrix, the hydroxyapatite microfiber bundle and the calcium silicate nanofiber is 8:2:0.1-3, preferably 8:2:0.5-2.5.
[0029] After obtaining the micro-nano composite membrane, it is preferably cut so that the orientation arrangement direction of the micro-nano fibers, i.e., hydroxyapatite micron fiber bundles and calcium silicate nanofibers in the obtained bionic intervertebral disc material is 30° to 60° with the horizontal direction, so as to more accurately imitate the structure of the intervertebral disc material. In some specific implementations, in the micro-nano fiber composite membrane, when the orientation arrangement direction of the micro-nano fibers (including hydroxyapatite micron fiber bundles and calcium silicate nanofibers) in the sodium alginate matrix is 90°, it is preferred to cut the micro-nano composite membrane along the diagonal line so that the orientation arrangement direction of the hydroxyapatite micron fiber bundles and calcium silicate nanofibers in the micro-nano composite membrane is 45° with the horizontal direction.
[0030] After cutting, the micro-nano composite membrane is curled into a ring under the action of an adhesive to form an outer fiber ring. In some specific implementations, the adhesive is chitosan. Specifically, the present application uses a polytetrafluoroethylene tube as a template, and after coating the cut micro-nano composite membrane with a chitosan solution, the membrane is wound and curled along the polytetrafluoroethylene tube until a predetermined thickness is reached. After the obtained material is left to stand at room temperature, the template is removed to obtain an outer fiber ring. At this time, the outer fiber ring is actually formed by multiple fiber sheets, each fiber sheet independently includes a micro-nano composite membrane, the micro-nano composite membrane includes a sodium alginate matrix and micro-nano fibers oriented and arranged in the sodium alginate matrix, and the micro-nano fibers include hydroxyapatite micron fiber bundles and calcium silicate nanofibers; the micro-nano composite membrane may include a first micro-nano composite membrane and a second micro-nano composite membrane arranged in sequence, and the orientation arrangement direction of the micro-nano fibers in the first micro-nano composite membrane is 90° to the orientation arrangement direction of the micro-nano fibers in the second micro-nano composite membrane. It can also be considered that at this time, the orientation arrangement direction of the micro-nano fibers in the upper structure of the micro-nano fiber membrane and the orientation arrangement direction of the micro-nano fibers in the lower structure are 90°. In any fiber sheet, the orientation arrangement direction of the micro-nano fibers, that is, the hydroxyapatite micron fiber bundles and the calcium silicate nanofibers, is 45° to the vertical direction, and this structure can better imitate the lamellar structure of the outer fiber ring of the intervertebral disc.
[0031] In some specific implementations, the coating can be sprayed using a spray gun. The present application has no special restrictions on the diameter of the polytetrafluoroethylene tube, which can be selected as needed, such as 5mm, 10mm, etc. The template also makes the diameter of the bionic intervertebral disc material adjustable. The microstructure of the intervertebral disc annulus is imitated by multi-directional winding assembly of the micro-nano composite membrane, and the outer annulus is customized to improve its mechanical properties.
[0032] After the outer annulus fibrosus is prepared, the raw material for forming the gel-state nucleus pulposus is added into the cavity of the outer annulus fibrosus, and after freeze-forming, etching and cross-linking are performed to form the gel-state nucleus pulposus, thereby obtaining a bionic intervertebral disc material. In some specific implementations, the gel-state nucleus pulposus is a sodium alginate gel. Specifically, it can be prepared according to the following method:
[0033] Sodium alginate solution is added into the cavity of the outer annulus fibrosus, and after being frozen and formed, it is added into calcium chloride solution to form a gel nucleus pulposus through cross-linking, thereby obtaining a bionic intervertebral disc material.
[0034] The present application realizes the construction of a porous gel nucleus pulposus in the annulus fibrosus by unidirectional freezing and metal ion cross-linking, and finally realizes the construction of a bionic intervertebral disc material. The present application first prepares a sodium alginate solution, specifically dissolving sodium alginate in water. In some specific implementations, the concentration of the sodium alginate solution is 1wt%~5wt%, preferably 1.5wt%~4.5wt%, preferably 2wt%~4wt%. In some specific implementations, the present application preferably vacuums and removes bubbles in the sodium alginate solution.
[0035] After obtaining the sodium alginate solution, add it into the cavity of the outer fiber ring, make the liquid level of the sodium alginate solution flush with the cavity, and shape it under freezing conditions. In the present application, the freezing temperature is preferably -40℃~-10℃, preferably -30℃~-20℃, and freeze until the sodium alginate solution is formed.
[0036] After the sodium alginate is formed, the obtained material is added to the calcium chloride solution. Under freezing conditions, the sodium alginate frozen body is gradually etched in the calcium chloride solution, and the solid-liquid interface is pushed inward to achieve solvent exchange and ion crosslinking. The metal ions diffuse to the outer wall of the sodium alginate frozen body for crosslinking to form a gel nucleus pulposus tightly combined with the outer fiber ring to obtain a bionic intervertebral disc material. In some specific implementations, the calcium chloride solution is preferably a pre-cooled calcium chloride solution, and the calcium chloride solution is preferably an ethanol solution of calcium chloride. The concentration of calcium chloride is preferably 0.05M~0.2M, and more preferably 0.1M~0.15M. In some specific implementations, the freezing temperature is preferably -20℃~-5℃, and preferably -15℃~-10℃.
[0037] In the bionic intervertebral disc material prepared by the present application, the outer fiber ring is formed by winding a multilayer micro-nano composite film with micro-nano fibers arranged in an oriented manner under the action of an adhesive. This structure is similar to the microstructure of the intervertebral disc fiber ring. The compounding of micro-nano fibers improves the structural stability, resilience and compression resistance of the bionic intervertebral disc material. In addition, the thickness and diameter of the bionic intervertebral disc material provided by the present application are controllable, which is conducive to its application in coping with intervertebral disc degenerative diseases.
[0038] The present application provides a bionic intervertebral disc material, comprising an outer fiber ring and a gel-state nucleus pulposus arranged inside the outer fiber ring;
[0039] The outer fiber ring includes multiple fiber layers and adhesives arranged between the fiber layers;
[0040] Each fiber sheet layer independently comprises a micro-nano composite membrane, wherein the micro-nano composite membrane comprises a sodium alginate matrix and micro-nano fibers oriented and arranged in the sodium alginate matrix, wherein the micro-nano fibers comprise hydroxyapatite micron fiber bundles and calcium silicate nanofibers;
[0041] The mass ratio of the sodium alginate matrix, the hydroxyapatite micron fiber bundle and the calcium silicate nanofiber is 8:2:0.1-3.
[0042] The bionic intervertebral disc material provided in the present application adopts a compound of micro-nano fibers, in which the nanofibers are filled in the gaps of the directionally arranged micron fibers, thereby improving the utilization efficiency of the organic-inorganic interface. Compared with the bionic intervertebral disc material prepared by only containing one type of micron fiber or one type of nanofiber, synergistic enhancement is achieved, and the mechanical properties of the material are greatly improved.
[0043] In some specific implementations, the mass ratio of the sodium alginate matrix, hydroxyapatite micron fiber bundle and calcium silicate nanofiber is 8:2:0.5~2.5. Experimental results show that the compounding of hydroxyapatite micron fiber bundle and calcium silicate nanofiber is the key to improving the mechanical properties of bionic intervertebral disc materials. If the amount of calcium silicate nanofiber is too low, its mechanical properties will not be significantly improved. If the amount exceeds a certain ratio, its mechanical properties will tend to decrease.
[0044] In some specific implementations, in the micro-nano composite membrane, the hydroxyapatite micron fiber bundles and the calcium silicate nanofibers are oriented in the sodium alginate matrix, that is, the hydroxyapatite micron fiber bundles and the calcium silicate nanofibers are arranged in a single direction, and the calcium silicate nanofibers can fill the gaps in the hydroxyapatite nanofibers, thereby improving the mechanical properties of the fiber sheets, and thereby improving the mechanical properties of the bionic intervertebral disc material.
[0045] In some specific implementations, the hydroxyapatite micron fiber bundle is a micron-level fiber bundle formed by self-assembly of hydroxyapatite fibers, the diameter of the hydroxyapatite fibers is 15nm~30nm, the diameter of the fiber bundle formed by self-assembly is 1μm~2μm, and the length is greater than 20μm. In some specific implementations, the calcium silicate nanofiber is a nanometer-level fiber with a diameter of 20nm~30nm and a length of 2μm~3μm.
[0046] In order to further increase the mechanical properties of bionic intervertebral disc materials, in the bionic intervertebral disc material provided in the present application, the micro-nano composite membrane includes a first micro-nano composite membrane and a second micro-nano composite membrane arranged in sequence, and the orientation arrangement direction of the micro-nano fibers in the first micro-nano composite membrane is distributed at 90° to the orientation arrangement direction of the micro-nano fibers in the second micro-nano composite membrane, which can better resist tensile loads.
[0047] In order to further increase the mechanical properties of the bionic intervertebral disc material, in any layer of fiber sheets, the micro-nano fibers, i.e., hydroxyapatite micron fiber bundles and calcium silicate nanofibers, are oriented at 45° to the horizontal direction. This structure is similar to the microstructure of the intervertebral disc and can improve the ability of the bionic intervertebral disc to resist complex loads.
[0048] In some specific implementations, the gel-state nucleus pulposus is sodium alginate gel. The sodium alginate gel is a gel formed in situ in the cavity of the outer annulus fibrosus, has good bonding force with the outer annulus fibrosus, and can resist the osmotic pressure of compression.
[0049] The bionic intervertebral disc material provided by the present application has a multi-scale hierarchical ordered structure, good bio-friendliness, stability, and is simple and easy to obtain. Moreover, the intervertebral disc material with a multi-scale structure has a large control space, and can accurately imitate the angle between the collagen fiber and the horizontal axis by changing the angle of the fiber in the outer annulus fibrosus: that is, when other experimental conditions remain unchanged, it is only necessary to perform a certain angle of successive spiral deflection brushing and sliding of the commercial brush adsorbed with the HAP-CS / SA mixed solution; the size of the bionic intervertebral disc can also be further controlled to meet the actual customization needs.
[0050] More importantly, the bionic intervertebral disc material assembled by the synergistic combination of micro-nano fibers has good mechanical properties. Compared with the bionic intervertebral disc material prepared by containing only one type of micron fiber or nanofiber, the nanofibers are filled in the gaps of the directionally arranged micron fibers, which improves the utilization efficiency of the organic-inorganic interface and achieves synergistic enhancement. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a SEM photo of the HAP micron fiber provided in the examples of the present application;
[0052] Figure 2 This is a SEM photo of CS nanofibers provided in the examples of this application;
[0053] Figure 3 This is a SEM photograph of the HAP-CS / SA film prepared in Example 1 at a scale of 50 μm;
[0054] Figure 4 This is a SEM photograph of the HAP-CS / SA film prepared in Example 1 at a scale of 50 μm;
[0055] Figure 5 The tensile stress-strain curves of the HAP-CS / SA films prepared in the examples and comparative examples of the present application;
[0056] Figure 6 Statistics of Young's modulus of HAP-CS / SA films prepared in the examples and comparative examples of the present application;
[0057] Figure 7 The tensile strength statistics of the HAP-CS / SA films prepared in the examples and comparative examples of the present application;
[0058] Figure 8 Schematic diagram of the annulus fiber assembly;
[0059] Fig. 9 Schematic diagram of preparation of gel-state nucleus pulposus;
[0060] Fig.10 This is a schematic diagram of the construction of bionic intervertebral disc materials;
[0061] Fig.11 This is a photo of the bionic intervertebral disc material;
[0062] Fig.12 The SEM images of the bionic intervertebral disc materials prepared in the examples and comparative examples;
[0063] Fig.13 The wet compression modulus of the bionic intervertebral disc material prepared in the embodiment and the comparative example;
[0064] Fig.14 The wet compression properties of the bionic intervertebral disc materials prepared in the examples and comparative examples;
[0065] Fig.15 This is a photo of the compression and resilience performance of the bionic intervertebral disc material prepared in Example 1 of the present application;
[0066] Fig.16 The results of immersing the bionic intervertebral disc material provided in Example 1 of the present application in PBS;
[0067] Fig.17 This is a SEM photo of the HAP-CS / SA film prepared in Example 2 at a scale of 50 μm;
[0068] Fig.18 This is a SEM photo of the HAP-CS / SA film prepared in Example 2 at a scale of 50 μm;
[0069] Fig.19 This is a SEM photograph of the HAP-CS / SA film prepared in Example 3 at a scale of 20 μm;
[0070] Fig. 20 This is a SEM photograph of the HAP-CS / SA film prepared in Example 3 at a scale of 20 μm. DETAILED DESCRIPTION
[0071] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0072] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0073] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0074] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0075] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0076] The present application provides a bionic intervertebral disc material, comprising an outer fiber ring and a gel-state nucleus pulposus arranged inside the outer fiber ring;
[0077] The outer fiber ring includes multiple fiber layers and adhesives arranged between the fiber layers;
[0078] Each fiber sheet layer independently comprises a micro-nano composite membrane, wherein the micro-nano composite membrane comprises a sodium alginate matrix and micro-nano fibers oriented and arranged in the sodium alginate matrix, wherein the micro-nano fibers comprise hydroxyapatite micron fiber bundles and calcium silicate nanofibers;
[0079] The mass ratio of the sodium alginate matrix, the hydroxyapatite micron fiber bundle and the calcium silicate nanofiber is 8:2:0.1-3.
[0080] The bionic intervertebral disc material provided by the present application has a multi-scale hierarchical ordered structure, good bio-friendliness, stability, and is simple and easy to obtain. Moreover, the intervertebral disc material with a multi-scale structure has a large control space, and can accurately imitate the angle between the collagen fiber and the horizontal axis by changing the angle between the fiber in the outer annulus fibrosus and the horizontal direction: that is, when other experimental conditions remain unchanged, it is only necessary to perform a certain angle of successive spiral deflection brushing and sliding of the commercial brush adsorbed with the HAP-CS / SA mixed solution; the size of the bionic intervertebral disc can also be further controlled to meet the actual customization needs.
[0081] More importantly, the bionic intervertebral disc material assembled by the synergistic combination of micro-nano fibers has good mechanical properties. Compared with the bionic intervertebral disc material prepared by containing only one type of micron fiber or nanofiber, the nanofibers are filled in the gaps of the directionally arranged micron fibers, which improves the utilization efficiency of the organic-inorganic interface and achieves synergistic enhancement.
[0082] The bionic intervertebral disc material and the preparation method thereof provided by the present application are further described below in conjunction with the embodiments.
[0083] Example 1
[0084] Step 1: Synthesis of hydroxyapatite (HAP) microfibers:
[0085] HAP microfibers were synthesized by solvothermal method using calcium oleate precursor. First, NaOH (6.3 g) aqueous solution (90 mL) was slowly dripped into a mixed solution of oleic acid (63 mL), methanol (36 mL) and deionized water (81 mL) and stirred vigorously for 30 minutes. Second, CaCl2 (2 g) aqueous solution (72 mL) was slowly added to the above mixture and stirred for 30 minutes to complete ion exchange and form calcium oleate. Third, NaH2PO4•2H2O (5.62 g) aqueous solution (108 mL) was dripped into the above mixture and reacted for 30 minutes to produce amorphous calcium phosphate and obtain a precursor suspension. The obtained precursor suspension was transferred to a 500 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 180 °C for 24 hours. After the autoclave was cooled to room temperature, the HAP fibers at the bottom were collected, washed three times with ethanol and deionized water respectively, and then dispersed in deionized water.
[0086] See also Figure 1 , Figure 1 The SEM photo of the HAP micron fiber provided in the embodiment of the present application is Figure 1 It can be seen that the diameter of the HAP fiber is 15 nm to 30 nm, but it self-assembles into a fiber bundle with a diameter of 1 μm to 2 μm; the length of the HAP fiber is more than 20 μm.
[0087] Step 2: Synthesis of calcium silicate (CS) nanofibers:
[0088] Ca(NO3)2•4H2O (23.6 g) aqueous solution (200 mL) was added dropwise to NaSiO3•9H2O (28.42 g) aqueous solution (200 mL). After reacting for 30 min, it was transferred to a 500 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 200 °C for 24 h. After the autoclave was cooled to room temperature, the CS fibers at the bottom were collected, washed three times with deionized water, and then dispersed in deionized water.
[0089] See also Figure 2 , Figure 2 The SEM photo of CS nanofibers provided in the present application is Figure 1 It can be seen that the diameter of the CS fiber is 20nm~30nm, and the length is 2μm~3μm.
[0090] Step 3: Preparation of HAP-CS / SA film:
[0091] Take 0.2 g of HAP microfiber dispersion based on HAP microfiber and 0.2 g of CS fiber dispersion based on CS fiber, a total of 50 mL solution, add 0.8 g of SA powder to the mixed fiber dispersion, mix and stir for 3 hours until the mixed system is uniform and evacuate to remove bubbles in the system. Use a commercial brush that absorbs the mixed solution to slide and brush on a glass substrate heated to about 80 °C in advance at a speed of about 2 cm / s in a single direction, and obtain a HAP-CS / SA film with a specific thickness and orientation by multiple brushing.
[0092] See also Figure 3 and Figure 4 , Figure 3 This is a SEM photo of the HAP-CS / SA film prepared in Example 1 at a scale of 50 μm. Figure 4 This is a SEM photo of the HAP-CS / SA film prepared in Example 1 at a scale of 50 μm. Figure 3 and Figure 4 It can be seen that the present application prepared a well-oriented HAP-CS / SA film.
[0093] The tensile test of the ternary film was carried out using a universal testing machine. The results are shown in Figure 5 , Figure 6 and Figure 7 , Figure 5 : is the tensile stress-strain curve of the HAP-CS / SA film prepared in the examples and comparative examples of the present application, Figure 6 The Young's modulus statistics of the HAP-CS / SA films prepared in the examples and comparative examples of the present application are as follows: Figure 7The tensile strength statistics of the HAP-CS / SA films prepared in the examples and comparative examples of this application are shown in FIG. Figure 5 , Figure 6 and Figure 7 It can be seen that the HAP-CS / SA film prepared in the embodiment of the present application has good tensile properties.
[0094] Step 4: Assembly of the annulus fiber:
[0095] After ten unidirectional brushings, the glass substrate was rotated 90° to prepare a 90° staggered HAP-CS / SA film. The prepared composite film was cut into thin strips with a width of 5 mm along the diagonal line. Figure 8 , Figure 8 Figure 1 is a schematic diagram of fiber ring assembly. First, a spray gun 1 is used to evenly spray a thin layer of chitosan 3 on the slender film 2. The sprayed slender film is wrapped around a polytetrafluoroethylene tube 4 with a diameter of 5 mm until the total diameter reaches 10 mm. The curled tube is wrapped with a sealing film and left to stand at room temperature for 12 hours, after which the polytetrafluoroethylene column template in the center of the tube is removed.
[0096] Step 5: Preparation of gel nucleus pulposus:
[0097] Dissolve 2 g of sodium alginate powder in 98 mL of deionized water and stir until the system is clear to prepare a 2 wt.% sodium alginate solution for later use. Fig. 9 , Fig.10 and Fig.11 , Fig. 9 Schematic diagram of the preparation of gel nucleus pulposus. Fig.10 This is a schematic diagram of the construction of bionic intervertebral disc materials. Fig.11 is a photo of the bionic intervertebral disc material. The annulus fibrosus 61 obtained in step 4 was placed on a -20 ℃ cold stage 62. After standing for 2 minutes, a 2% SA solution from which bubbles had been removed was dripped into the hollow cavity of the annulus fibrosus 61 until the SA solution was frozen and formed. The assembled material was placed in a pre-cooled 0.1M CaCl2 ethanol solution, and the SA was simultaneously subjected to ice etching and CaCl2 etching at -10 ℃ and normal pressure. 2+ After ion cross-linking for 12 hours, a bionic intervertebral disc material with a diameter of 10 mm and a height of 5 mm was obtained.
[0098] The bionic intervertebral disc material was subjected to tearing loading and the microstructure of the interface between the thin layers was observed by scanning electron microscopy (SEM). Fig.12 , Fig.12 This is the SEM image of the bionic intervertebral disc material prepared in Example 1. Fig.12 It can be seen that the bionic intervertebral disc material has numerous white chitosan strips, which confirms that the interlayer interface is tightly bonded, indicating that the bionic intervertebral disc has good structural stability.
[0099] The bionic intervertebral disc material was subjected to a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested to obtain the compression modulus of the bionic intervertebral disc. The results are shown in Fig.13 and Fig.14 , Fig.13 is the wet compression modulus of the bionic intervertebral disc material prepared in the embodiment and the comparative example, Fig.14 The wet compression properties of the bionic intervertebral disc materials prepared in the examples and comparative examples are shown in FIG. Fig.13 and 14 It can be seen that the bionic intervertebral disc material prepared in Example 1 of the present application has good compression performance.
[0100] The bionic intervertebral disc material was compressed with a force of 500N and then waited for its rebound. The results are shown in Fig.15 , Fig.15 This is a photo of the compression and resilience performance of the bionic intervertebral disc material prepared in Example 1 of the present application. Fig.15 It can be seen that the bionic intervertebral disc material prepared in the present application has good compression resilience.
[0101] The bionic intervertebral disc material was immersed in phosphate buffered saline (PBS). Fig.16 , Fig.16 The results of immersing the bionic intervertebral disc material provided in Example 1 of the present application in PBS show that it does not disintegrate after being immersed for six months.
[0102] It can be seen that the bionic intervertebral disc material prepared in the embodiment of the present application has an outer annulus fibrosus and a porous gel-state nucleus pulposus structure with tightly connected interlayer interfaces, and has good structural stability, resilience and compression resistance.
[0103] Example 2
[0104] The difference from Example 1 is that in the preparation process of the HAP-CS / SA film, the amount of CS fiber dispersion used is 0.15 g.
[0105] See also Fig.17 and Fig.18 , Fig.17 This is a SEM photo of the HAP-CS / SA film prepared in Example 2 at a scale of 50 μm. Fig.18 This is a SEM photo of the HAP-CS / SA film prepared in Example 2 at a scale of 50 μm. Fig.17 and Fig.18 It can be seen that the present application prepared a well-oriented HAP-CS / SA film.
[0106] The tensile test of the ternary film was carried out using a universal testing machine. The results are shown in Figure 5 , Figure 6 and Figure 7 , Figure 5 : is the tensile stress-strain curve of the HAP-CS / SA film prepared in the examples and comparative examples of the present application, Figure 6 The Young's modulus statistics of the HAP-CS / SA films prepared in the examples and comparative examples of the present application are as follows: Figure 7 The tensile strength statistics of the HAP-CS / SA films prepared in the examples and comparative examples of this application are shown in FIG. Figure 5 , Figure 6 and Figure 7 It can be seen that the HAP-CS / SA film prepared in the embodiment of the present application has good tensile properties.
[0107] The obtained bionic intervertebral disc material was subjected to tearing loading and the fine structure of the interface between thin layers was observed by scanning electron microscopy (SEM). The results showed that the bionic intervertebral disc material contained numerous white chitosan strips, which confirmed the tight adhesion between the layers and indicated that the bionic intervertebral disc had good structural stability.
[0108] The bionic intervertebral disc material was tested using a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested, and the results showed that the bionic intervertebral disc material prepared in the embodiment of the present application had good compression performance.
[0109] The obtained bionic intervertebral disc material was subjected to a rebound compression test, and the results showed that the bionic intervertebral disc prepared in the embodiment of the present application had good compression rebound elasticity.
[0110] The obtained bionic intervertebral disc material was immersed in phosphate buffered saline (PBS), and the results showed that it did not disintegrate after being immersed for six months.
[0111] It can be seen that the bionic intervertebral disc material prepared in the embodiment of the present application has an outer annulus fibrosus and a porous gel-state nucleus pulposus structure with tightly connected interlayer interfaces, and has good structural stability, resilience and compression resistance.
[0112] Example 3
[0113] The difference from Example 1 is that in the preparation process of the HAP-CS / SA film, the amount of CS fiber dispersion used is 0.25 g.
[0114] See also Fig.19 and Fig. 20 , Fig.19 This is a SEM photo of the HAP-CS / SA film prepared in Example 3 at a scale of 20 μm. Fig. 20 This is a SEM photo of the HAP-CS / SA film prepared in Example 3 at a scale of 20 μm. Fig.19 and Fig. 20It can be seen that the present application prepared a well-oriented HAP-CS / SA film.
[0115] The tensile test of the ternary film was carried out using a universal testing machine. The results are shown in Figure 5 , Figure 6 and Figure 7 , Figure 5 : is the tensile stress-strain curve of the HAP-CS / SA film prepared in the examples and comparative examples of the present application, Figure 6 The Young's modulus statistics of the HAP-CS / SA films prepared in the examples and comparative examples of the present application are as follows: Figure 7 The tensile strength statistics of the HAP-CS / SA films prepared in the examples and comparative examples of this application are shown in FIG. Figure 5 , Figure 6 and Figure 7 It can be seen that the HAP-CS / SA film prepared in the embodiment of the present application has good tensile properties.
[0116] The obtained bionic intervertebral disc material was subjected to tearing loading and the fine structure of the interface between thin layers was observed by scanning electron microscopy (SEM). The results showed that the bionic intervertebral disc material contained numerous white chitosan strips, which confirmed the tight adhesion between the layers and indicated that the bionic intervertebral disc had good structural stability.
[0117] The bionic intervertebral disc material was tested using a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested, and the results showed that the bionic intervertebral disc material prepared in the embodiment of the present application had good compression performance.
[0118] The obtained bionic intervertebral disc material was subjected to a rebound compression test, and the results showed that the bionic intervertebral disc prepared in the embodiment of the present application had good compression rebound elasticity.
[0119] The obtained bionic intervertebral disc material was immersed in phosphate buffered saline (PBS), and the results showed that it did not disintegrate after being immersed for six months.
[0120] It can be seen that the bionic intervertebral disc material prepared in the embodiment of the present application has an outer annulus fibrosus and a porous gel-state nucleus pulposus structure with tightly connected interlayer interfaces, and has good structural stability, resilience and compression resistance.
[0121] Example 4
[0122] The difference from Example 1 is that in the preparation process of the HAP-CS / SA film, the amount of CS fiber dispersion used is 0.05 g.
[0123] The tensile test of the ternary film was carried out using a universal testing machine. The results are shown in Figure 5 , Figure 6 and Figure 7, Figure 5 : is the tensile stress-strain curve of the HAP-CS / SA film prepared in the examples and comparative examples of the present application, Figure 6 The Young's modulus statistics of the HAP-CS / SA films prepared in the examples and comparative examples of the present application are as follows: Figure 7 The tensile strength statistics of the HAP-CS / SA films prepared in the examples and comparative examples of this application are shown in FIG. Figure 5 , Figure 6 and Figure 7 It can be seen that the HAP-CS / SA film prepared in the embodiment of the present application has good tensile properties.
[0124] The obtained bionic intervertebral disc material was subjected to tearing loading and the fine structure of the interface between thin layers was observed by scanning electron microscopy (SEM). The results showed that the bionic intervertebral disc material contained numerous white chitosan strips, which confirmed the tight adhesion between the layers and indicated that the bionic intervertebral disc had good structural stability.
[0125] The bionic intervertebral disc material was tested using a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested, and the results showed that the bionic intervertebral disc material prepared in the embodiment of the present application had good compression performance.
[0126] The obtained bionic intervertebral disc material was subjected to a rebound compression test, and the results showed that the bionic intervertebral disc prepared in the embodiment of the present application had good compression rebound elasticity.
[0127] The obtained bionic intervertebral disc material was immersed in phosphate buffered saline (PBS), and the results showed that it did not disintegrate after being immersed for six months.
[0128] It can be seen that the bionic intervertebral disc material prepared in the embodiment of the present application has an outer annulus fibrosus and a porous gel-state nucleus pulposus structure with tightly connected interlayer interfaces, and has good structural stability, resilience and compression resistance.
[0129] Example 5
[0130] The difference from Example 1 is that in the preparation process of the HAP-CS / SA film, the amount of CS fiber dispersion used is 0.1 g.
[0131] The tensile test of the ternary film was carried out using a universal testing machine. The results are shown in Figure 5 , Figure 6 and Figure 7 , Figure 5 : is the tensile stress-strain curve of the HAP-CS / SA film prepared in the examples and comparative examples of the present application, Figure 6 The Young's modulus statistics of the HAP-CS / SA films prepared in the examples and comparative examples of the present application are as follows: Figure 7The tensile strength statistics of the HAP-CS / SA films prepared in the examples and comparative examples of this application are shown in FIG. Figure 5 , Figure 6 and Figure 7 It can be seen that the HAP-CS / SA film prepared in the embodiment of the present application has good tensile properties.
[0132] The obtained bionic intervertebral disc material was subjected to tearing loading and the fine structure of the interface between thin layers was observed by scanning electron microscopy (SEM). The results showed that the bionic intervertebral disc material contained numerous white chitosan strips, which confirmed the tight adhesion between the layers and indicated that the bionic intervertebral disc had good structural stability.
[0133] The bionic intervertebral disc material was tested using a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested, and the results showed that the bionic intervertebral disc material prepared in the embodiment of the present application had good compression performance.
[0134] The obtained bionic intervertebral disc material was subjected to a rebound compression test, and the results showed that the bionic intervertebral disc prepared in the embodiment of the present application had good compression rebound elasticity.
[0135] The obtained bionic intervertebral disc material was immersed in phosphate buffered saline (PBS), and the results showed that it did not disintegrate after being immersed for six months.
[0136] It can be seen that the bionic intervertebral disc material prepared in the embodiment of the present application has an outer annulus fibrosus and a porous gel-state nucleus pulposus structure with tightly connected interlayer interfaces, and has good structural stability, resilience and compression resistance.
[0137] Comparative Example 1
[0138] The difference from Example 1 is that during the preparation of the HAP-CS / SA film, no CS fiber dispersion was added.
[0139] The tensile test of the ternary film was carried out using a universal testing machine. The results are shown in Figure 5 , Figure 6 and Figure 7 , Figure 5 : is the tensile stress-strain curve of the HAP-CS / SA film prepared in the examples and comparative examples of the present application, Figure 6 The Young's modulus statistics of the HAP-CS / SA films prepared in the examples and comparative examples of the present application are as follows: Figure 7 The tensile strength statistics of the HAP-CS / SA films prepared in the examples and comparative examples of this application are shown in FIG. Figure 5 , Figure 6 and Figure 7It can be seen that the tensile properties of the HAP-CS / SA film prepared without adding CS fiber dispersion are lower than those of the film prepared with adding CS fiber dispersion.
[0140] The bionic intervertebral disc material was tested using a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested to obtain the compression modulus of the bionic intervertebral disc. The results are shown in Fig.13 and Fig.14 , Fig.13 is the wet compression modulus of the bionic intervertebral disc material prepared in the embodiment and the comparative example, Fig.14 The wet compression properties of the bionic intervertebral disc materials prepared in the examples and comparative examples are shown in FIG. Fig.13 and 14 It can be seen that the bionic intervertebral disc material prepared in the comparative example of the present application has poor compression performance.
[0141] Comparative Example 2
[0142] The difference from Example 1 is that, during the preparation of the HAP-CS / SA film, no HAP fiber dispersion is added.
[0143] The bionic intervertebral disc material was tested using a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested to obtain the compression modulus of the bionic intervertebral disc. The results are shown in Fig.13 and Fig.14 , Fig.13 is the wet compression modulus of the bionic intervertebral disc material prepared in the embodiment and the comparative example, Fig.14 The wet compression properties of the bionic intervertebral disc materials prepared in the examples and comparative examples are shown in FIG. Fig.13 and 14 It can be seen that the bionic intervertebral disc material prepared in the comparative example of the present application has poor compression performance.
[0144] Comparative Example 3
[0145] The difference from Example 1 is that during the preparation of the HAP-CS / SA film, no CS fiber dispersion liquid and CS fiber dispersion liquid are added.
[0146] The bionic intervertebral disc material was tested using a universal mechanical testing machine at a speed of 0.5 mm min −1 The compression rate was tested to obtain the compression modulus of the bionic intervertebral disc. The results are shown in Fig.13 and Fig.14 , Fig.13 is the wet compression modulus of the bionic intervertebral disc material prepared in the embodiment and the comparative example, Fig.14 The wet compression properties of the bionic intervertebral disc materials prepared in the examples and comparative examples are shown in FIG. Fig.13 and 14It can be seen that the bionic intervertebral disc material prepared in the comparative example of the present application has poor compression performance.
[0147] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A bionic intervertebral disc material, comprising an outer annulus fibrosus and a gel-like nucleus pulposus arranged inside the outer annulus fibrosus; The outer fiber ring includes multiple fiber layers and adhesives arranged between the fiber layers; Each fiber sheet layer independently comprises a micro-nano composite membrane, wherein the micro-nano composite membrane comprises a sodium alginate matrix and micro-nano fibers oriented and arranged in the sodium alginate matrix, wherein the micro-nano fibers comprise hydroxyapatite micron fiber bundles and calcium silicate nanofibers; The mass ratio of the sodium alginate matrix, the hydroxyapatite microfiber bundle and the calcium silicate nanofiber is 8:2:0.1-3; In any fiber sheet, the orientation direction of the micro-nano fibers forms an angle with the horizontal direction.
2. The bionic intervertebral disc material according to claim 1, characterized in that: The mass ratio of the sodium alginate matrix, the hydroxyapatite micron fiber bundle and the calcium silicate nanofiber is 8:2:0.5-2.
5.
3. The bionic intervertebral disc material according to claim 1, characterized in that: The diameter of the hydroxyapatite micron fiber bundle is 1 μm to 2 μm, and the length is greater than or equal to 20 μm; The calcium silicate nanofiber has a diameter of 20 nm to 30 nm and a length of 2 μm to 3 μm.
4. The bionic intervertebral disc material according to any one of claims 1 to 3, characterized in that: The micro-nano composite membrane comprises a first micro-nano composite membrane and a second micro-nano composite membrane which are arranged in sequence, and the orientation arrangement direction of the micro-nano fibers in the first micro-nano composite membrane is distributed at 90° to the orientation arrangement direction of the micro-nano fibers in the second micro-nano composite membrane.
5. The bionic intervertebral disc material according to claim 4, characterized in that: In any fiber layer, the orientation and arrangement direction of the micro-nano fibers are staggered with the orientation and arrangement direction of the micro-nano fibers in the adjacent fiber layer; In any fiber sheet, the orientation direction of the micro-nano fibers is distributed at 45° to the horizontal direction.
6. The bionic intervertebral disc material according to any one of claims 1 to 3, characterized in that: The gel-state nucleus pulposus is sodium alginate gel.
7. A method for preparing a bionic intervertebral disc material, comprising the following steps: a) mixing a micro-nano fiber dispersion and sodium alginate, and applying unidirectionally on a substrate to orient the micro-nano fibers in the sodium alginate matrix to obtain a micro-nano composite membrane; the micro-nano fibers include hydroxyapatite micron fiber bundles and calcium silicate nanofibers; The mass ratio of the sodium alginate matrix, the hydroxyapatite microfiber bundle and the calcium silicate nanofiber is 8:2:0.1-3; b) keeping the orientation arrangement direction of the micro-nano fibers at an angle to the horizontal direction, and curling the micro-nano composite film into a ring under the action of an adhesive to form an outer fiber ring having multiple fiber sheets; c) adding the raw material for forming the gel nucleus pulposus into the cavity of the outer annulus fibrosus, freeze-forming and cross-linking to form the gel nucleus pulposus, thereby obtaining the bionic intervertebral disc material.
8. The preparation method according to claim 7, characterized in that: Step a) specifically includes: The micro-nano fiber dispersion and sodium alginate are mixed, and the micro-nano fibers are unidirectionally brushed on the substrate in a first direction to orient the micro-nano fibers in the sodium alginate matrix; and the micro-nano fibers are unidirectionally brushed in a second direction to obtain a micro-nano composite film; The first direction and the second direction are distributed at 90°.
9. The preparation method according to claim 8, characterized in that: The step b) specifically comprises: The micro-nano composite film is cut along the diagonal line, and the cut micro-nano composite film is curled into a ring under the action of chitosan, so that the orientation arrangement direction of the micro-nano fibers in any fiber layer is distributed at 45 degrees to the horizontal direction.
10. The preparation method according to claim 9, characterized in that: The step c) specifically comprises: Sodium alginate solution is added into the cavity of the outer annulus fibrosus, and after being frozen and formed, it is added into calcium chloride solution to form a gel nucleus pulposus through cross-linking, thereby obtaining a bionic intervertebral disc material.
